What DNA Viral Genomic Rearrangements Tell Us about Persistence - Imperiale, Michael J. (J Virol, 2014)
Understanding the life cycle and pathogenesis of animal viruses requires that we have systems in which the viruses can replicate and cause disease. For the latter, we rely upon animal models or information that we can obtain from studying natural infections of humans and other animals. For the former, however, we are largely dependent on the availability of cell culture systems in which viruses can be propagated to investigate the molecular mechanisms of viral replication. For many years, it was assumed that replication in culture provided an accurate description of the life cycle of the organism. In this Gem, we will discuss two viruses, polyomavirus and cytomegalovirus, in which cell culture systems have accidentally provided unique potential insights into viral replication and persistence in their hosts.